Heritage education at University. Strategies for evaluating the cultural urban heritage in the educational process of young people - Sagrario Ortiz Núñez (Universidad del Magdalena, 2014)
This article presents part of the results of the research "Images of city and cultural expressions of the urban landscape with patrimonial value for young people in Medellin" developed by members of two research groups of the Universidad Pontificia Bolivariana, during 2011 -Semillero de Investigación en Urbanismo, SIUR and Semillero Integrado de Educación en Ciencias-. This research proposes urban cultural heritage as a pedagogical tool in the education of young university students. To this end, strategies that allowed enhancing the assets valuation of the environment surrounding were designed, increasing in this way the sense of belonging and social identity.